Oscillatory Behaviour of a First-Order Neutral Differential Equation in relation to an Old Open Problem - K. C. Panda; R. N. Rath; S. K. Rath (International Journal of Mathematics and Mathematical Sciences)
In this paper, we obtain sufficient conditions for oscillation and nonoscillation of the solutions of the neutral delay differential equation yt−∑j=1kpjtyrjt′+qtGygt−utHyht=ft, where pj and rj for each j and q,u,G,H,g,h, and f are all continuous functions and q≥0,u≥0,ht<t,gt<t, and rjt<t for each j. Further, each rjt, gt, and ht⟶∞ as t⟶∞. This paper improves and generalizes some known results.